Genotoxic response of Java medaka (Oryzias javanicus) to glyphosate-based herbicide - Yusof, Shahrizad; Muham Said, Nor Farina; Bahali, Nur Haryanti; Ismail, Ahmad (Department of Biology, Faculty of Mathematics and Natural Sciences, Bogor Agricultural University, 2015)
Java medaka (Oryzias javanicus) is an emerging test organism for ecotoxicological studies. This study was carried out to assess the genotoxic response of Java medaka to glyphosate-based herbicide in terms of micronucleus and nuclear abnormality induction. Java medaka embryos and adult Java medaka were exposed to different concentrations of glyphosate-based herbicide (10, 20, 30, 40 and 50 ppm) in ambient temperature for 10 days and 48 hours respectively. The embryos and fish were then sacrificed. The gills were dissected from the fish. Slides of the blood from the embryos and gills were prepared. The lowest concentration where the induction of micronucleus and nuclear abnormalities in the embryos occurred was in exposure to 30 ppm. In the gills, the induction of nuclear abnormalities started to occur in exposure to 10 ppm while micronucleus induction in the embryo started in exposure to 30 ppm. Apart from micronucleus, the nuclear abnormalities scored during this study were notched nucleus, lobed nucleus, blebbed nucleus, vacuolated nucleus and binuclei. Nuclear abnormalities such as micronuclei are considered as well established indicators of cytotoxicity and genetic toxicology. The induction of micronucleus and nuclear abnormalities in glyphosate-based herbicide-exposed Java medaka shows that the fish is a suitable test organism for genotoxicity study. Utilisation of both the embryos and adult fish has been beneficial to evaluate toxicity of pollutants. The induction of micronucleus and nuclear abnormalities can serve as good biomarkers in detecting early biological changes caused by environmental pollutants.